Closed-loop operated time-based accelerometer - Dias, Rosana A. (2012)
A high-resolution, high dynamic range capacitive accelerometer based on pull-in time measurement is described in this paper. The high sensitivity of pull-in time can be used to implement high performance accelerometers, but non-linearity and low dynamic range compromise device performance. A closed-loop approach using an electrostatic actuation mechanism to control the duration of the pull-in time is presented, which addresses the low dynamic range problem. Capacitive parallel-plates structures were used and the preliminary experimental results of closed-loop operation under several acceleration values confirm the potential of this technique and the overall accelerometer concept. The results show an accelerometer with high sensitivity (better than 6 μV/μg) and improved linearity over a large dynamic range.